Determinants Affecting Human Resource Development Of Small And Medium Enterprises In Dong Nai Province - Thu Thuy, Dr. Le; Thanh Tam, Dr. Phan (Social Science Learning Education Journal, 2017)
The Vietnam now has around 500,000 SMEs are active, of which there are about 15,000 businesses in Dong Nai province. Although there is no small amount, but these businesses are very small scale and very low level of development was weak in terms of capital, technology, management capability and experience lack of access to information, land, markets ... domestic competition was hard, when participating in the FTA, the SMEs concerns facing strong competition from other companies is very strong and the countrys elite you. However, while SMEs have difficulties inherent characteristics such but it is important for SMEs not need to be big, strong, but growth needs to be very fast, very sure.The research results showed that there were 250 SMEs of Dong Nai province that interviewed and answered about 25 questions from 10/01/2016 to 15/10/2016. The researchers had analyzed KMO test, the result of KMO analysis used for multiple regression analysis. There are five factors, which included of factors following: Component 1 was appreciation of work done (X1), Component 2 was interesting work (X2), Component 3 was income (X3), Component 4 is conditions/working environment (X4) and Component 5 was welfare policy (X5) which affecting the human resource development of small and medium enterprises with 5 % significance level. The research results were processed from SPSS 20.0 software. The parameters of the model estimated by Least - Squares Method tested for the model assumption with 5% significance level.